Manipulation of the Fascial System Applied During Acute Inflammation of the Connective Tissue of the Thoracolumbar Region Affects Transforming Growth Factor-β1 and Interleukin-4 Levels: Experimental Study in Mice - França, Maria Elisa Duarte; Sinhorim, Larissa; Martins, Daniel Fernandes; Schleip, Robert; Machado-Pereira, Nicolas A. M. M.; de Souza, Gabriel Melo; Horewicz, Verônica Vargas; Santos, Gilmar Moraes (Frontiers in Physiology, 2020)
Fascia can become rigid and assume a fibrotic pattern due to inflammatory processes. Manipulation of the fascial system (MFS), manual technique targeting connective tissues, is commonly used in clinical practice in pain management. We aimed to verify MFS effects on the connective tissue inflammatory changes in mice. Swiss mus musculus male mice (n = 44) were distributed into groups: carrageenan without treatment (Car, n = 11), carrageenan with MFS (Car+MFS, n = 12), Saline without treatment (n = 10), and saline with MFS (Saline+MFS, n = 11). IL-4, IL-6, tumor necrosis factor (TNF), transforming growth factor beta 1 (TGF-β1), and monocyte chemoattractant protein 1 (MCP-1) levels were verified by ELISA. Neutrophil (Ly-6G), macrophage (F4/80), and nitric oxide synthase 2 (NOS-2) were identified using western blot. The MFS protocol was applied from first to third day after inflammation of the connective tissue of the thoracolumbar region. There was a significant MFS effect on IL-4 (p = 0.02) and TGF-β1 (p = 0.04), without increasing MCP-1, TNF, and IL-6 levels (p > 0.05) on thoracolumbar region from Car+MFS, in comparison with Saline. Ly-6G in Car+MFS presented lower levels when compared with Saline (p = 0.003) or Saline+MFS (0.003). NOS-2 levels were lower in Car+MFS than in Saline+MFS (p = 0.0195) or Saline (p = 0.003). MFS may have anti-inflammatory effect, based on TGF-β1 and IL-4. IL-4 may have inhibited neutrophil migration. Lower levels of NOS-2 may be linked to the lack of macrophages, which are responsible for NOS-2 expression.